Music of the night in Ipoh - New Straits Times, Dennis Chua (2008)
The Perak Society Of Performing Arts' (PSPA) International Ensemble is back on Aug 15 with Music Of The Night, a new repertoire featuring eight internationally acclairned musicians from the United states, South Korea, Hong kong and Malaysia